Preparação, caracterização, estudo fotoluminescente e cinético dos complexos de terras raras coordenados a picratos com contra cátions imidazólicos - Alex dos Santos Borges (2013)
This work reports the synthesis, characterization and investigation of the photoluminescent properties of pentakis(picrate) complexes of Eu3+, Gd3+, Sm3+, with counter-cations 1-n-butyl-3- methylimidazole (BMIm+), 1-n-butyl-3-ethylimidazole (BEIm+) and 1,3-dibutylimidazol(BBIm+) and of tetrakis(picrate) complex of Nd3+, Sm3+, Eu3+, Gd3+ and Tb3+, with the countercation 1-ethyl-3-methylimidazolium (EMIm+). A kinetic study of thermal decomposition of the picrate ionic liquids 1-n-butyl-3-methylimidazole (BMIm-Pic), 1-n-butyl-3-ethylimidazole(BEIm-Pic), 1,3-dibutylimidazol (BBIm-Pic), and 1-ethyl-3-methylimidazolium (EMIm-Pic); and of the tetrakis(picrate) complex of Nd3+ was also carried out. The synthesized compounds were characterized by microanalysis of C, H and N, absorption spectroscopy in the infrared and UV-Vis region, complexometric titration with EDTA, molarconductance, thermal analysis (TG/DTG and DTA) and X-ray diffraction (single crystal and powder). The ligands were characterized by CHN, IR and Nuclear Magnetic Resonance (1HNMR and 13C {1H}). The structure of BMIm-Pic was determined by X-ray crystallography. The results obtained by CHN and complexometric titration suggests the general formulas (EMIm)2[TR(Pic)4(H2O)2]Pic (TR3+ = Nd3+, Sm3+, Eu3+, Gd3+, Tb3+) and (LI)2[TR(Pic)5] (LI = BMIm+, BEIm+ and BBIm+; TR3+ = Sm3+, Eu3+, Gd3+). The IR spectra obtained for the complexes indicates that some of the picrate groups are coordinated as bidentate ligands through the phenolic oxygen and one of the oxygens of a nitro group. The preparation of anhydrous and hydrated complexes was confirmed by TG/DTG. The residues of the complexes were identified as their rare earth oxides (TR2O3). The kinetic study of thermal decomposition was carried out by the methods of model-free Kissinger, Flynn-Wall-Ozawa (FWO) and Kissinger-Akira-Sunose (KAS) with four heatingrates (5, 10, 15 and 20 ºC min-1) for the ionic liquids, EMIm-Pic, BMIm-Pic, BEIm-Pic and BBIm-Pic, and seven heating rates of (2.5, 5, 10, 15, 20, 25 and 30 ºC min-1 ) for the Nd3+complex. Furthermore, a study of the thermodynamic activation parameters (deltaG, deltaH and deltaS)of the Nd3+ complex was carried out. Single crystals of (EMIm)2[TR(Pic)4(H2O)2]Pic (TR = Nd3+, Sm3+, Eu3+, Gd3+, Tb3+),(BEIm)2[TR(Pic)5] and (BBIm)2[TR(Pic)5] were obtained and their structures were determined by X-rays diffraction studies. The complexes crystallize in a triclinic system with space group P and are nine-coordinated. The geometry of the complexes [TR(Pic)4(H2O)2]- are a distorted tricapped trigonal prism, whereas for [Eu(Pic)5]2- the geometry is a distorted monocapped square antiprism.The phosphorescence spectra of Gd3+ complexes exhibited a broad and characteristic emission band of the picrate ligand. The T1 state energies of the picrate ligand varies between 18500 and 19500 cm-1, which is highest than the 4G5/2 and 5D0 states of Sm3+ and Eu3+ions, respectively and less than 5D4 state of Tb3+ ion. The efficiency of the energy transfer, Ligand-TR3+ (TR3+ = Sm3+ and Eu3+), is confirmed by their excitation spectra (high intensity of the ligand excitation band) and emission (they have no ligand phosphorescence band, but onlycharacteristics emission bands of TR3+ ions). Emission spectra of Sm3+ and Eu3+ showed sharp bands assigned to transitions 4G5/2 6HJ (where J = 5/2, 7/2, 9/2 and 11/2) and 5D0 7FJ (where J = 0, 1, 2, 3, 4, 5 and 6), respectively, split on the maximum number (J +1/2)-components and (2J +1)-component, respectively, suggesting that both ions Sm3+ and Eu3+ ion are located a chemical environment of low symmetry. Based on spectral data of the Eu3+ complexes the experimental intensity parameters (2 and 4), radiative (Arad) and non-radiative (Anrad) rates of spontaneous emission, and the quantumefficiency of emission of the level 5D0 (), which presented the following order of emission for complexes of the Eu3+: (EMIm)2[Eu(Pic)4(H2O)2]Pic < (BMIm)2[TR(Pic)5] < (BEIm)2[TR(Pic)5]< (BBIm)2[TR(Pic)5], were determined. The energy transfer processes from the picrate ligand to Eu3+ were investigated by thetheoretical models Sparkle/PM3. The theoretical structure of Eu3+ complexes is very similar with the structure determined experimentally by X-ray diffraction. It was also observed that the coordination polyhedron around the Eu3+ ion (in the theoretical structures) corroborates with thesplit of the bands assigned to the 5D0 7FJ transitions. The energy transfer rates determined by Sparkle/PM3 provide the theoretical quantum yield, theoretical intensity parameters, theoretical values of the radiative and non-radiative rates of spontaneous emission, besides theoretical emission efficiency, that are in good agreement with the experimental data, suggesting the viability of theoretical models on studies of the trivalent rare earth coordination compounds. The photoluminescent behavior exhibited by the europium complexes indicates that thissystem acts as Light Converters Molecular Devices (LCMD).